Phytochemical and Pharmacological Review of Dendrophthoe falcata - Kota1, Manjula Talluri2, Sarvani Manthri1, Chaitanya Sravanthi (Journal of Phytology, 2011)
Nature is blessed with variety of plants having medicinal properties one of which is Dendrophthoe falcata widely distributed in India. D. falcata is a hemiparasitic plant having almost 401 plant hosts of which Sugar apple (Annona squamosa), and epicortical roots as on Sapota (Achras zapota), guava (Psidium guajava), pomegranate (Punica granatum), mango (Mangifera indica) are commonly known. It is indigenously said to have potential medicinal properties. It is reported to have diuretic, wound healing, anti microbial, antihelminthic, anti fertility, anti oxidant, anti cancer, anti diabetic, anti hyperlipidemic, anti hypertensive activities. This paper presents a limited review on the pharmacognostic, phytochemical and pharmacological activities of D. falcata. Key words: Dendrophthoe falcata, Hemiparasitic Sarvani Manthri et al. Pharmacognostic, Phytochemical and Pharmacological Review of Dendrophthoe falcata. J Phytol 3/3 (2011) 18-25.